PENERAPAN ENTREPRENEURSHIP BOOKSEBAGAI MEDIA PEMBELAJARAN UNTUK MENUMBUHKANKECAKAPAN HIDUP (VOKASIONAL) PADA MATA PELAJARANEKONOMI DI SMA N 8 YOGYAKARTA - dan Iin Khairunissa, Raras Gistha Rosardi, Chandra Widyadewa, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This research focuses on life skills education particularly on vocational skills. Theobjective of this research is to know how the entrepreneurship book can grow the lifeskill of vocational learning.This research is a classroom action research which employed quantitative andqualitative method. The research was conducted in two cycles. The subject of the researchwas the students of Economic subject at Grade XI of Social Class. The sample of thisresearch was thirty students. They were given Entrepreneurship book as learning media.Then, they were assigned to design jobs based on the club; like Academic Club, HandycraftClub, Art Club, Culinary Club, Entertainment Club, and Fashion Club. Each club shouldmake company description, both in group observation sheet and individual observationsheet.The result of the first cycle shows that in individual observation 40% students werein a good category and 60% students in average category. Meanwhile, in groupobservation the average score for every club was 20. The observation was done towardssix clubs. In the evaluation of Cycle 1 it was known that Academic Club got the best pointin essays effort and the supreme score of individual estimation was 97.5 and the scorewas 40. On The cycle 2 in individual observation 76% students were in good categoryand 24% students in enough categories. Meanwhile, for group observation averagely20.4 by ideal score every club was 20. The observation was done toward 6 groups. In theevaluation of Cycle 2, it was known that Academic Club got the best point to essays toknow effort potency. Meanwhile, the individual estimation of supreme score was 98.5and the estimated score was 60. It means that there is an increase from Cycle 1.Key words: Entrepreneurship Book, life skills, vocational